Echoes of the pandemic: Contrasting COVID-19 outbreaks in northern Peru - Pereira-Victorio, César Johan (2024)
Peru reported the second-highest COVID-19 cases in Latin America, after Brazil. The first COVID-19 wave occurred between March– December 2020, and the second occurred between January–September 2021. The differences between these waves remain largely unknown, and there is no comparison between them in Peru. We evaluated the variation in the clinical and epidemiological components of COVID-19-affected patients in both waves in northern Peru by a retrospective study using the clinical follow-up database of Lambayeque and the epidemiological notification form database of NotiWeb. The COVID-19-associated factors during the two waves were determined using simple and multiple regression analysis, and the prevalence ratio (PR) was estimated. During the second wave of COVID-19, there was an increase in cough symptoms in 12.1%, odynophagia in 5.0%, and chills in 16.0% compared with the first wave. The second wave was marked by a higher proportion of affected adolescents and children and a greater percentage of respiratory symptoms than the first wave. © Failoc-Rojas VE et al. This is an open access article distributed under the terms of the Creative Commons Attribution License (CC-BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.